Analysis of Green Constitutions in Environmental Law Related to Spatial Planning and Balance of IKN Development in Indonesia - Mardiana; Saputri, Syabila (Ipso Jure, 2024)
This study analyzes the implementation of the green constitution in environmental law concerning spatial planning and the development of the National Capital (IKN) in Indonesia. The Green Constitution emphasizes environmental protection as a human right, as stated in Article 28H of the 1945 Constitution. The research focuses on the challenges of IKN development in East Kalimantan, including the risks of environmental damage such as deforestation and ecosystem disruption. The Indonesian government is committed to maintaining 80% of the IKN area as green space, but effective implementation requires stricter law enforcement and greater involvement of local communities. The methodology used is a normative juridical approach through the analysis of applicable legal regulations. The results highlight the importance of applying environmentally friendly technologies and ecosystem restoration as efforts to maintain environmental sustainability amidst development. Collaboration between stakeholders, including the government, private sector, and community, is essential to achieving a balance between economic growth and environmental preservation. This study recommends strengthening environmental law enforcement, increasing local community involvement in the development process, and the use of technologies that support sustainable development.